Optimasi Tanah Napa sebagai Adsorben Ion Logam Kromium (IV) - Mawardi Anwar; Rahmi Khairun Nisa (Departemen Kimia FMIPA UNP, 2013)
A study concerning the determination of the optimum conditions for the adsorption of chromium (VI) by tanah napa adsorbent from Aripan, Solok. Tanah napa containing high silica and alumina are 63.20% and 16.55%, levels of silica and alumina in the tanah napa almost the same levels with natural zeolite, which can be used as adsorbent. In this research studied the influence of various parameters that affect the capacity of tanah napa uptake to Cr(VI), the pH of the solution, the initial concentration of solution, adsorbent particle size, heating temperature adsorbent and eluent flow rate. The results of this study indicate that the optimum pH is 4, the optimum initial concentration of 250 mg/L, while the particle size and adsorbent optimum heating temperature is 850 mm and 125°C, and the optimum flow rate is 20 drops/min. Using the Langmuir adsorption isotherm equation obtained maximum absorption capacity of the tanah napa to Cr(VI) that is equal to 0.911 mg/g.